PEMBIAKAN NEMATODA PATOGEN SERANGGA (Rhabditida: Heterorhabditis DAN Steinernema) PADA MEDIA SEMI PADAT - . Chaerani (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Field application of entomopathogenic nematodes (EPN) is still hampered by inefficient mass production. The aim of this study was to compare three published in vitro media (medium Wouts, Bedding and Han) for mass propagation of three indigenous EPNs (Heterorhabditis indicus PLR2, H. indicus isolate 5, and Steinernema T96) and one commercial strain (S. carpocapsae #25). The media were impregnated in shredded polyurethane sponge, pre-inoculated with symbiotic bacteria of each nematode and inoculated with the respective infective juveniles (Ijs) of the nematode. Nematode yields at three weeks after nematode inoculation were inconsistent accross replications and experiments and generally not significantly influenced by the kind of media tested. Average yields showed that the highest IJ productions were obtained on medium Han for H. indicus PLR2 (0,4×105 Ijs/g medium) and for S. carpocapsae #25 (2.2×105 IJs/g medium), and on medium Wouts for H. indicus isolate 5 (6.5×105 Ijs/g medium) and Steinernema T96 (1.5×105 IJs/g medium). The Ijs’ body were significantly shorter than those of in vivo propagated, which may impair the nematode pathogenicity. Modifications of the propagation technique and media formulation are needed to improve the quantity and quality of Ijs.